Skrining Kesehatan Dalam Upaya Meningkatkan Status Kesehatan Remaja Di Kota Metro - M.Ridwan; Septi Widiyanti; Yuliawati Yuliawati; Rofana Aghniya (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Routine health checks/screenings are preventive promotive efforts mandated to be carried out by regents/mayors in accordance with Permendagri no 18/2016 with the aim of encouraging people to recognize risk factors for non-communicable diseases (PTM) related to behavior and make immediate control efforts at the individual, family level and society; encouraging the discovery of physiological risk factors that have the potential to cause PTM, namely overweight and obesity, high blood pressure, high blood sugar levels, sensory disturbances and mental disorders. The purpose of this activity is to find out earlier the status of reproductive health in young women at SMK Muhammadiyah 3 Metro. Screening consists of measuring weight, measuring height, measuring BMI, measuring LILA and personal hygiene screening. Screening results showed that 1.9% of students had low TB (less than 148.9cm), 28.3% had a thin BMI status, 5% BMI Overweight and 18.5% had KEK (Chronic Energy Deficiency) with LILA<23 ,5cm. From this activity it can be concluded that the health problems of adolescents at Muhammadiyah 3 Metro Vocational School are quite varied so that further intervention is needed so as not to cause unwanted health impacts in the future.